1965
DOI: 10.1029/jz070i011p02469
|View full text |Cite
|
Sign up to set email alerts
|

Neutron monitor mass absorption coefficients at Chicago and climax during solar cycle 19 (1954-1963)

Abstract: The dependence of the neutron monitor mass absorption coefficient on 11‐year changes in the primary cosmic‐ray spectrum was investigated for the monitors at Chicago, Illinois, and Climax, Colorado, using a modified single regression method. The analysis of hourly intensity and pressure values for 733 days at Chicago and 1000 days at Climax during the period 1954–1963 revealed no significant variation at either station. The mean value of the coefficient at Chicago is −0.938±0.007%/mm Hg; at Climax it is −1.010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…While the temperature effect is generally determined by the overall profile of the atmosphere from the level of origin to the detection level, the barometric effect is determined only by the pressure at sea level. The rate of the detected cosmic ray depends on the amount of material traversed above the detector, and the barometric pressure is taken as a measure of this mass [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While the temperature effect is generally determined by the overall profile of the atmosphere from the level of origin to the detection level, the barometric effect is determined only by the pressure at sea level. The rate of the detected cosmic ray depends on the amount of material traversed above the detector, and the barometric pressure is taken as a measure of this mass [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…There would be essentially no change in • at Po ~ 15 bv over the solar cycle because the total neutron intensity is changed only about 5% and •n is constant. At a station such as Climax (X --500 mm Itg), there is little or no muon contamination, and • changes by less than 3% at this cutoff rigidity (Po • 3 by), which explains the absence of a long-term change in •n [Forman, 1965].…”
mentioning
confidence: 99%
“…An approximate quantitative cheek of the effect of water vapor on neutron monitor intensities is afforded by comparison of the barometric pressure coefficients determined for two neutron monitors at different altitudes for which approximate characteristic atmospheric water vapor contents can be determined. Comparison of the pressure coefficients reported for the Climax, Colorado, monitor [Forman, 1965] at an altitude of 3500 meters with the Denver, Colorado, monitor [Kisselbach and Chasson, 1965] has indicated that the coefficient for the Denver monitor is usually somewhat larger than that for the Climax monitor. Time variability in the difference has also been qualitatively indicated.…”
mentioning
confidence: 99%